Syntactic Analysis of Sentence Structure in “The Hobbit: An Unexpected Journey” - Erwin Suhendra; Novian Zaini; Shinta Ayu Pertiwi (LPPM Universitas Bumigora Mataram, 2022)
Hobbit: An Unexpected Journey” movies also to describe sentence structures through tree-diagram. This study used a mix method research strategy on sentence structure that answers the types of sentences used in stages of plot and tree diagram portrayal in The Hobbit: An Unexpected Journey movie, aiming at finding the types of sentences in stages of plot and portrayal in tree diagram. Data of this research are qualitative in type and the sentences are taken from The Hobbit: An Unexpected Journey movie. The data is obtained through listening and note-taking method. It examines the structure of sentences using a syntactic approach in stages of plot depicted in the tree diagram. Data collected in the movie is then calculated using Bungin’s formula to find out the percentage of each sentence. In this analysis all types of sentence structures are found in the movie were simple sentences, compound sentences, complex sentences, and compound-complex sentences. The Hobbit: An Unexpected Journey movie has 1298 sentences in the film. The one that dominate the film are simple sentences which amount to 809 or 62% of the total data obtain ed, followed by compound sentences totaling 308 or 24%, then there are complex sentences totaling 125 or 10% and the last are compound-complex sentences amounting to 56 or 4% of the total data. And the tree diagram shows that the sentence has a really various phrases such as noun, verb, preposition, adjective and adverb phrase.